Analisis Pertimbangan Hakim Dalam Penjatuhan Putusan Bebas Terhadap Tindak Pidana Pencabulan - Octo Iskandar; Robiah (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
In the context of law enforcement, the court has a very important role. Judges who are executors of activities in the field of justice must pay attention to values that develop and live in society and must also master written legal norms (das solen). It is hoped that the court's decision can be used as a correction and record whether it has fulfilled a sense of justice or vice versa based on existing legal facts so that it can be seen whether there is harmonization and synchronization between das solen and das sein. For this reason, in terms of imposing criminal sanctions on every perpetrator of a crime, it really requires the active role of a judge and also law enforcement officials to be able to apply the law fairly. One of the legal issues related to the criminal act of obscenity which is interesting to study is the Supreme Court Decision Number 550 K/Pid.sus/2020 in which the Judge passed an acquittal. The results of the legal research, in this decision the child's testimony seemed to be ignored by the judge, the judge only focused on 1 witness and the results of the post mortem stated that there were abrasions caused by a blunt object but the victim's hymen was still intact, according to the judge the results of the post mortem were not sufficient to confirm that there has been an act of obscenity, in this case the judge did not interpret what was meant by obscenity, it does not mean that if the victim's hymen is still intact, it means that there has never been an act of obscenity at all.